Work Motivation as a Mediation of Compensation and Work Environment on Employee Performance - Bambang Guritno; Henry Yuliamir; Enik Rahayu; Hendrajaya, Hendrajaya (Pusat Riset dan Inovasi Nasional, 2022)
There are still employee complaints that the compensation is not consistent with the concept of justice, the existing facilities at the research site are insufficient to perform community service duties, the facilities that require quantity and quality improvements. This study aims to prove the effect of compensation, facilities, and work environment on the job satisfaction of environmental employees in Kendal Regency. This research is included in quantitative research using SPSS 16 and research design using associative approach. The associative approach was carried out with the aim of finding the effect of compensation and work environment on performance mediated by work motivation. The time of the research was from January 2020 to April 2020. The population in this study were all district employees, totaling 89 (eighty nine) individuals. The sampling method in this study uses saturated sampling, where due to the limited number of populations, it is possible for the population to be sampled. The sample in this study in this study were district employees totaling 88 (eighty eight) people (minus the researcher). The results show that There are effects of compensation and work environment on work motivation, employees in Semarang Regency. There are effects of compensation and work environment, work motivation on the Performance of Environmental Employees in sub-districts of Semarang Regency. There is an effect of the work environment on work motivation and does not have an impact on the performance of environmental employees in sub-districts of Semarang Regency.